'Hunger has brought us into this jungle': understanding mobility and immobility of Bengali immigrants in the Chittagong Hills of Bangladesh. (4th July 2017) - Siraj, Nasrin; Bal, Ellen
ABSTRACT: The recent history of the Chittagong Hills in Bangladesh is marked by ongoing conflicts between minority (non-Muslim and non-Bengali) locals and state-sponsored (Bengali Muslim) immigrants. In general, these immigrants are framed as land grabbers who have been receiving protection from a pro-Bengali military force. We propose instead, that the understanding of these Bengalis as a homogenous category of mobile perpetrators fails to take into account their complex histories as mobile landless peasants. Our ethnographic research reveals that the framing of the local minorities and the mobile Bengalis as two antagonistic categories with opposing interests obscures the fact that both categories have fallen victim to very similar regimes of mobilities and immobilities of the state and national and local (political, economic and military) elites. Here, we reject binary thinking that counterpoises mobility and immobility as two antagonistic concepts and argue that mobility and immobility are intrinsically related and their relationship is asymmetrical.